Bladder Infection - Study 108 operative cases - Baracco Gandolfo, Víctor (1951)
Normally bile is found in the bile ducts free of germs, only in the lower segment of the common bile duct can be found sometimes the presence of Escherichia coli, with no pathological disorders (Kirschner). In pathological circumstances bacterial infection in the different diseases of the biliary tract shows an extremely varied flora. Until now, they have agreed not authors on the predominant type of infection. Naunyn considers Bacterium coli as the main agent in inflammatory diseases of the biliary tract, and recent research consider staphylococcus (Hunter-Muller, Gundermann). The diversity of results may be explained by trying the techniques used in research, methods of storage, examination of material from autopsies and operations or the use of anaerobic media (Ozaki), missing most communications.